Review on Blue Perovskite Light-Emitting Diodes: Recent Advances and Future Prospects - Ge, Chuangye; Fang, Qianru; Lin, Haoran; Hu, Hanlin (Frontiers in Materials, 2021)
Perovskite-based light-emitting diodes (PLEDs) have emerged as a promising alternative owning to the excellent optoelectronic properties including narrow emission linewidths, high photoluminescence quantum yield (PLQY), tunable emission wavelength and high color purity. Over the past several years, significant progress have been obtained for green, red, and near infrared PLEDs with high external quantum efficiency (EQE) over 20%. However, the development of blue PLEDs has been limited by several technical issues including poor film quality, inefficient device structure, higher trap density and so on. To overcome these drawbacks with improved PLQY and EQE, we summarize and analyze the recent advances towards the development of three dimensional (3D), two dimensional (2D) and quasi- 2D perovskites film employing composition and/or dimensional engineering. Moreover, utilization of perovskite nanocrystals (NCs) is also considered as feasible strategy for the realization of highperformance blue PLEDs. We systematically evaluate the performance of sky-blue, pure-blue and deep blue PLEDs based on different perovskite materials. Finally, future prospective are proposed to promote the development of efficient blue PLEDs.